A Zeolitic Octahedral Metal Oxide with Ultra‐Microporosity for Inverse CO2/C2H2 Separation at High Temperature and Humidity. (1st August 2022) - Ma, Baokai; Li, Denan; Zhu, Qianqian; Li, Yanshuo; Ueda, Wataru; Zhang, Zhenxin
Abstract: Separation of CO2 /C2 H2 to obtain pure C2 H2 presents a challenge for the chemical industry. CO2 ‐selective adsorbents are favored because of the convenient separation process. However, there are only a few CO2 ‐selective adsorbents that can effectively isolate CO2 from CO2 /C2 H2, and there is almost no research on CO2 /C2 H2 separation under harsh conditions, such as with high temperatures and humidities. Herein, a zeolitic octahedral metal oxide based on ϵ‐Keggin polyoxometalates is utilized for separations of CO2 /C2 H2 at high temperatures and humidities. Single gas adsorption measurements show that the material only adsorbs CO2 with almost no C2 H2 taken up. Dynamic competitive adsorption experiments show that the material efficiently separates CO2 /C2 H2, and highly pure C2 H2 is obtained directly. The robust material maintains a high separation performance at 333 K with 18.12 % water. The high stability of the material enables reuse without loss of separation performance. Abstract : Ultra‐microporous zeolitic octahedral metal oxide is used for CO2 capture over C2 H2 to obtain highly pure C2 H2 directly. The material not only shows high separation performance at low temperatures but also at high temperatures and humidities.